The Effect of Combining N-Fertilization with Urease Inhibitors and Biological Preparations on Maize Biological Productivity - Povilas Drulis; Zita Kriaučiūnienė; Vytautas Liakas (Agronomy, 2022)
After evaluating the ecological and economic aspects, it is predicted that the use of urease inhibitors and biological preparations should reduce the risk of nutrient leaching by using fertilizers containing amide, ammonium, and nitrate forms of nitrogen and would increase nitrogen use efficiency. Moreover, with lower nitrogen fertilizer rates, it would be possible to achieve or even increase planned maize biomass yield. The field experiment was performed in 2019–2021 at the Experimental Station of Vytautas Magnus University Agriculture Academy. The soil of the experimental field was Endohipogleyic-Eutric Planasol. The aim of this study was to investigate the effect of urease inhibitors and biological preparations in combination with nitrogen fertilizers on the productivity of aboveground maize (Zea mays L.) biomass. A two-factor experiment was carried out: factor A included nitrogen fertilizer rates of (1) 100 kg N ha−1, (2) 140 kg N ha−1, and (3) 180 kg N ha−1; and factor B included the use of preparations of (1) no use of urease inhibitors (UIs) and biological preparations (BPs) (control), (2) the urease inhibitor ammonium thiosulphate (UI ATS), (3) the urease inhibitor (UI URN)—N-Butyl-thiophosphorus triamide (NBPT), (4) the biological preparation of suspension of humic and fulvic acids (BP HUM); and (5) the biological preparation (BP FIT) of suspension of Ascophyllum nodosum The studies showed that the dry matter yield of maize was significantly increased not only by increasing nitrogen fertilizer rates but also by the use of UIs and BPs. The highest dry matter yield of maize (24.1 t ha−1) was obtained with N180 fertilizer and UI ATS. UI ATS significantly increased the dry matter yield of the aboveground maize in all nitrogen fertilization backgrounds. The UIs and BPs tested had a greater and significant (p < 0.05) effect on the dry matter yield of maize at lower rates of N100 and N140 nitrogen fertilizer. Increasing nitrogen fertilizer rates up to N180 had a positive significant effect on dry matter yields of the aboveground part of maize, its cobs, leaves, and stems. Positive, moderate, strong, and very strong correlations were found in most cases between the latter variables. These correlations were statistically significant (r2 = 0.62–0.98). The UIs and BPs increased the efficiency of nitrogen fertilizer; therefore, the lower rates of nitrogen fertilizer (N100 and N140) could be used to produce maize productivity the same as that obtained with a high rate of nitrogen fertilizer (N180).